Early Entry Events in Echovirus 30 Infection - Vandesande, Helena (J Virol, 2020)
Echovirus 30 (E30), a member of the enterovirus B species, is a major cause of viral meningitis, targeting children and adults alike. While it is a frequently isolated enterovirus and the cause of several outbreaks all over the world, surprisingly little is known regarding its entry and replication strategy within cells. In this study, we used E30 strain Bastianni (E30B) generated from an infectious cDNA clone in order to study early entry events during infection in human RD cells. E30B required the newly discovered Fc echovirus receptor (FcRn) for successful infection, but not the coxsackievirus and adenovirus receptor (CAR) or decay-accelerating factor (DAF), although an interaction with DAF was observed. Double-stranded RNA replication intermediate was generated between 2 and 3 h postinfection (p.i.), and viral capsid production was initiated between 4 and 5 h p.i. The drugs affecting Rac1 (NSC 23766) and cholesterol (filipin III) compromised infection, whereas bafilomycin A1, dyngo, U-73122, wortmannin, and nocodazole did not, suggesting the virus follows an enterovirus-triggered macropinocytic pathway rather than the clathrin pathway. Colocalization with early endosomes and increased infection due to constitutively active Rab5 expression suggests some overlap and entry to classical early endosomes. Taken together, these results suggest that E30B induces an enterovirus entry pathway, leading to uncoating in early endosomes. IMPORTANCE Echovirus 30 (E30) is a prevalent enterovirus causing regular outbreaks in both children and adults in different parts of the world. It is therefore surprising that relatively little is known of its infectious entry pathway. We set out to generate a cDNA clone and gradient purified the virus in order to study the early entry events in human cells. We have recently studied other enterovirus B group viruses, like echovirus 1 (EV1) and coxsackievirus A9 (CVA9), and found many similarities between those viruses, allowing us to define a so-called “enterovirus entry pathway.” Here, E30 is reminiscent of these viruses, for example, by not relying on acidification for infectious entry. However, despite not using the clathrin entry pathway, E30 accumulates in classical early endosomes.